Сучасний стан та тенденції розвитку підприємств роздрібної торгівлі - Коптєва (Фадєєва), Ганна Миколаївна (My University, 2019)
У статті розглянуто сучасний стан, умови функціонування і розвиток торговельної галузі в Україні, а також чинники, які впливають на розвиток підприємств роздрібної торгівлі. На основі проведеного аналізу динаміки та структури підприємств роздрібної торгівлі України з’ясовано, що за останнє десятиріччя суттєво скоротилася кількість підприємств роздрібної торгівлі, на внутрішньому ринку працюють переважно малі підприємства. На основі аналізу статистичних даних Державної служби статистики України проаналізовано основні показники, які свідчать про розвиток галузі торгівлі. Проаналізовано динаміку та структуру роздрібного товарообороту і фінансових результатів підприємств роздрібної торгівлі України. Досліджено основні проблеми, які стримують розвиток ринку роздрібної торгівлі, та визначено тенденції розвитку підприємств роздрібної торгівлі.

The conditions of functioning and development of retail industry require a deep analysis to identify the key factors that influence economic development in Ukraine in general and, in particular, in retail. It is important not only to identify these factors but also to find out their place and role in the overall economic system. The purpose of this article is to study the current state of retail enterprises in Ukraine, to identify the conditions of their economic activity and to conduct the analysis of trends in retail industry. The article considers the current state, conditions of functioning and development of retail industry in Ukraine. The factors influencing the development of retail enterprises are identified. Based on the analysis of the dynamics and structure of retail enterprises in Ukraine, it was found that the number of these enterprises has significantly decreased over the past decade, small businesses dominate in the domestic retail market. Based on the statistical data provided by the State statistics service of Ukraine, the dynamics and structure of retail turnover and financial results of retail enterprises in Ukraine are analyzed. The obtained results show that during the period of 2010-2018 there was a huge growth of retail turnover (more than 2,4 times). At the same time financial results were unstable, although the number of unprofitable retail enterprises decreased. Based on the statistical data, the main factors favoring and hindering the development of Ukrainian retail are investigated, and the development trends of retail enterprises are estimated. The author also substantiates that the innovative economic development requires new approaches to conducting retail, taking into account European and world technologies in this field. The obtained analytical results allow the author to identify the overall positive dynamics, trends, and potential of the further development of the Ukrainian retail industry. All this is an important condition for the justification and development of necessary measures to increase the economic efficiency of the retail industry and to promote its dynamic development.
Current state and trends of retail enterprises
Keywords: торгівля; торговельне підприємство; торговельна галузь; товарообіг; фінансовий результат; trade; trade enterprise; trade industry; trade turnover; financial result